THE IMPACT OF MASS CUSTOMISATION ON THE QUALITY MANAGEMENT SYSTEM IN A SALES AND MARKETING ENVIRONMENT - Joubert, F.J.; Bekker, M.C. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: The introduction of a vehicle platform destined for world-wide export brought mass customi-sation to the South African subsidiary of a German luxury car manufacturer. This, together with a 29% head count reduction, a model range increase, stringent profitability targets and increased customer satisfaction demands, made the previous, unintegrated quality systems used in the Sales and Marketing Division obsolete. A quality management system (QMS) based on ISO 9002 was implemented. To solve some of the problems in the mass customisa-tion process, the principles of customer satisfaction and the measurement of internal processes were used to make recommendations for operational improvements. AFRIKAANSE OPSOMMING: Die produksie van voertuie wat in groot volumes w